The Gingerbread Man loose on the fire truck - Murray, Laura, 1970-; Lowery, Mike, 1980- (New York, NY : G.P. Putnam's Sons, 2013)
When the Gingerbread Man joins the children who made him on a school field trip to a fire station, he escapes being eaten by Spot the Dalmatian and rides along to a fire.
Keywords: Gingerbread men -- Juvenile fiction; Cookies -- Juvenile fiction; Fire departments -- Juvenile fiction; Fire prevention -- Juvenile fiction; School field trips -- Juvenile fiction; Stories in rhyme; Cookies -- Fiction; Fire departments -- Fiction; School field trips -- Fiction; Cookies; Fire departments; Fire prevention; Gingerbread men; School field trips; Cookies -- Juvenile fiction; Fire departments -- Juvenile fiction; Fire prevention -- Juvenile fiction; Gingerbread men -- Juvenile fiction; School field trips -- Juvenile fiction; Stories in rhyme; Stories in rhyme; Fiction; Juvenile works; Stories in rhyme